2018
DOI: 10.1038/s41537-018-0051-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fronto-striatal networks during cognitive control in unmedicated patients with schizophrenia and the effect of antipsychotic medication

Abstract: To understand the mechanism of cognitive control dysfunction in schizophrenia, it is critical to characterize brain function without the confounding effect of medication. It is also important to establish the extent to which antipsychotic medication restores brain function and whether those changes are related to psychosis improvement. Twenty-two patients with schizophrenia, initially unmedicated and after a 6-week course of risperidone, and 20 healthy controls (HC) studied twice, 6 weeks apart, performed an f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…Results of Stroop task-based BOLD fMRI signal in off-medication SZ patients and the longitudinal differences after 6 weeks of medication have been previously published ( 63 ). In the SN, off-medication SZ showed significantly less BOLD response in the ACC and insula compared to baseline HC during Stroop task performance.…”
Section: Resultsmentioning
confidence: 99%
“…Results of Stroop task-based BOLD fMRI signal in off-medication SZ patients and the longitudinal differences after 6 weeks of medication have been previously published ( 63 ). In the SN, off-medication SZ showed significantly less BOLD response in the ACC and insula compared to baseline HC during Stroop task performance.…”
Section: Resultsmentioning
confidence: 99%
“…This finding is supported by evidence that prefrontal-striatal functional connectivity is important for determining treatment response in antipsychotic-naïve patients with psychosis. For example, Cadena et al, 2018 , Cadena et al, 2019 ) reported increased ACC functional activity and functional connectivity between ACC and putamen from baseline to follow-up was associated with better treatment response (decrease in symptoms) following a 6-week course of antipsychotic medication (risperidone) ( Cadena et al, 2018 , Cadena et al, 2019 ). Sarpal et al (2016) also reported that resting-state striatal functional connectivity, including with ACC, was predictive of treatment response following a trial of second generation antipsychotic medication in first episode psychosis ( Sarpal et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other associations with dorsal circuit function and PLE severity implicate areas that are known to be affected by schizophrenia and subthreshold symptomatology. Abnormal structure and function of the ACC are frequently reported in both patients and high-risk individuals (29,(69)(70)(71)(72)(73)(74). Concordantly, ACC dysfunction is linked to a failure to update prior beliefs based on sensory experience, which may induce hallucinations (75).…”
Section: Dorsal Corticostriatal Coupling and Plesmentioning
confidence: 99%